2017
DOI: 10.1021/acsphotonics.7b00486
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Surface Illuminated Si Photodiode Using Microstructured Holes for Absorption Enhancements at 900–1000 nm Wavelength

Abstract: A surface-illuminated silicon photodiode with both high speed and usable external quantum efficiency from 900 to 1000 nm wavelength is highly desirable for intra/inter data center Ethernet communications, high performance computing, and laser radar application. Such Si photodiodes have the potential for monolithic integration to CMOS integrated circuits which can significantly reduce the cost of data transmission per gigabit below one US dollar. To overcome silicon's intrinsic weakness of absorption in these w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…Several types of microscale and nanoscale structures have been demonstrated in the absorption enhancement of energy conversion systems, such as solar cells [11,12] and thermophotovoltaic devices [13], including nanowires [10,11,14,15], nanorods [16], nanodisks [17], nanocones [18], nanopyramids [19,20], nanoholes [21,22], and other grating structures [23][24][25][26]. Our recent experimental studies [27,28] showed that an array of nanoholes integrated on a 2-μm-thick Si film effectively traps light with wavelengths between 800 and 950 nm and can be used to achieve a high EQE (40-60%) in Si photodetectors while ensuring ultrafast impulse response (full-width at half-maximum) of 30 ps. High-speed Geon-Si photodiodes with photon-trapping holes have also been demonstrated with improved EQE at wavelengths between 1200 and 1800 nm [29].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several types of microscale and nanoscale structures have been demonstrated in the absorption enhancement of energy conversion systems, such as solar cells [11,12] and thermophotovoltaic devices [13], including nanowires [10,11,14,15], nanorods [16], nanodisks [17], nanocones [18], nanopyramids [19,20], nanoholes [21,22], and other grating structures [23][24][25][26]. Our recent experimental studies [27,28] showed that an array of nanoholes integrated on a 2-μm-thick Si film effectively traps light with wavelengths between 800 and 950 nm and can be used to achieve a high EQE (40-60%) in Si photodetectors while ensuring ultrafast impulse response (full-width at half-maximum) of 30 ps. High-speed Geon-Si photodiodes with photon-trapping holes have also been demonstrated with improved EQE at wavelengths between 1200 and 1800 nm [29].…”
Section: Introductionmentioning
confidence: 91%
“…The thinner ring and the thicker opened ring are n-ohmic metal on n-mesa and p-ohmic metal on p-mesa, respectively. The detailed fabrication process and EQE characteristics of the photodiodes were reported in our previous studies [27,28]. Photodiodes with hole arrays arranged in hexagonal lattice, as shown in Figure 1D, were fabricated on both bulk Si and SOI wafers with hole diameters ranging from 630 to 1300 nm and periods from 900 to 1700 nm.…”
Section: Design and Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4,5 ] Another method of reducing the reflectance involves the creation of nanotextured semiconductor surfaces. [ 6–10 ] Nanotexturing fabricates subwavelength surfaces on a scale smaller than the wavelength of visible light; this results in discrete refractive‐index changes between the air and the semiconductor. [ 11,12 ] Continuous refractive index changes reduce the reflectance over a broad spectral range and are less influenced by the angle of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the applications using light-trapping structures have shown to be effective for enhancing absorption and expanding the operating band into longer wavelengths [9]. The micro-holes structures were used to scatter the normally incident light into the lateral propagation, forming guided modes, and increasing that allows using the thin layers of absorbing material more effective [12][13][14]. The effect was studied for mid-infrared material to increase the wavelength range of the conventional infrared materials [15].…”
Section: Introductionmentioning
confidence: 99%